Studies on microsporidian infection in Parapenaeopsis stylifera - Jose, Jasmine K (Indian Journal of Fisheries, 2011)
Parapenaeopsis stylifera, infected with microsporidians showed a distinct whitish discolouration in their abdominal musculature. Histopathological and histochemical studies of the infected tissues revealed the presence of microsporidian spores in different stages of development and accumulation of iron respectively